Avaliação pré-clínica do óleo de pequi (Caryocar coriaceum Wittm.) e emulsão a base deste para o tratamento da dermatite: formulação, caracterização e efeitos antimicrobiano e anti-inflamatório - Bezerra, Rafaela Gomes (2021)
The strategy used in this work was to continue the studies of our research group with the fixed oil of the fruit pulp of the pequi (Caryocar coriaceum Wittm.) and thymol to contribute to the development of an emulsion that helps in the treatment of dermatitis and opportunistic infections caused by Staphylococcus aureus. The current pharmacotherapy for the treatment of dermatitis, a disease that affects about 44% of people worldwide, has limitations related to efficacy and its side effects. Studies have proven the anti-inflammatory activity of pequi fixed oil in experimental models of inflammation, as well as the antimicrobial effect of thymol against S. aureus. Thus, the aim of the present study was to evaluate anti-inflammatory and antimicrobial activities of the fixed oil of Caryocar coriaceum (OFCC) and the emulsion based on it and thymol. Therefore, OFCC was characterized (CG) and evaluated as possible cytotoxicity in human neutrophils (LDH, MTT). The emulsion, as well as its main asset (OFCC), were evaluated for anti-inflammatory effect in a model of irritant contact dermatitis induced by TPA in mice, with determination of the possible mechanism of action, as well as in an in vitro model of inflammation (human neutrophils). The antimicrobial activity was investigated against S. aureus ATCC 6538P and six non-resistant clinical strains, with determination of minimum inhibitory concentration (MIC) and minimum lethal concentration (CLM). The OFCC was characterized with oleic acid (52.26%) and palmitic acid (29.80%) as major components, which did not prove to be cytotoxic and had an anti-inflammatory effect by partially inhibiting the neutrophil degranulation induced by PMA expressed by the reduction the release of myeloperoxidase (MPO), reduced TPA-induced ear edema in mice and modulated cytokines (TNF-α and IL-10) in an unprecedented way in this model of inflammation in vivo. The OFCC emulsion was characterized and it was observed, in addition to physical-chemical stability, an increase in its antimicrobial effect with the addition of thymol. It was also possible to observe that the emulsion had an anti-inflammatory effect by reducing the release of myeloperoxidase (MPO) in neutrophils and a significant reduction in TPA-induced ear edema in mice. However, when assessing the concentration of cytokines (TNF-α and IL-10), modulation was not observed. This indicates the need for further experiments investigating other cytokines to suggest the real mechanism by which the OFCC and thymol emulsion promotes its anti-inflammatory effect.